Exploring the molecular basis of heterosis for plant breeding. Issue 3 (9th May 2019) - Liu, Jie; Li, Mengjie; Zhang, Qi; Wei, Xin; Huang, Xuehui
Abstract: Since approximate a century ago, many hybrid crops have been continually developed by crossing two inbred varieties. Owing to heterosis (hybrid vigor) in plants, these hybrids often have superior agricultural performances in yield or disease resistance succeeding their inbred parental lines. Several classical hypotheses have been proposed to explain the genetic causes of heterosis. During recent years, many new genetics and genomics strategies have been developed and used for the identifications of heterotic genes in plants. Heterotic effects of the heterotic loci and molecular functions of the heterotic genes are being investigated in many plants such as rice, maize, sorghum, Arabidopsis and tomato. More and more data and knowledge coming from the molecular studies of heterotic loci and genes will serve as a valuable resource for hybrid breeding by molecular design in future. This review aims to address recent advances in our understanding of the genetic and molecular mechanisms of heterosis in plants. The remaining scientific questions on the molecular basis of heterosis and the potential applications in breeding are also proposed and discussed. Abstract : Heterosis, or hybrid vigor, refers to the phenomenon that hybrids show superior performance over their parents. Although it has been widely exploited in crop breeding, little is known about the underlying mechanism. Recent progresses on genetic and molecular basis of heterosis are summarized in this review for a better understanding.